A PEMBENTUKAN KARAKTER SISWA DENGAN METODE KETELADANAN DI SDN UNGGUL TERPADU PADANG PARIAMAN: Pendahuluan, Literatur Review, Metode Penelitian, Hasil dan Pembahasan, Kesimpulan - rumi, Rumi Atur Rahmat; Febriani, Febriani (Journal Education And Islamic Studies, 2025)
This study aims to enhance the development of students’ Islamic character through the implementation of the exemplary method at SDN Unggul Terpadu Padang Pariaman. The research employed a Classroom Action Research (CAR) design, referring to a modified Kemmis and McTaggart model, which included the stages of planning, action implementation, observation, and reflection. The research subjects were 20 students, with data collected through observation, questionnaires, and interviews. The findings revealed a significant improvement in students’ Islamic character. In the first cycle, only 30% of students demonstrated positive behavioral changes, though inconsistently. After refining the strategy in the second cycle, the proportion increased to 85%. Specific improvements were observed in worship discipline (from 35% to 75%), honesty (from 25% to 80%), responsibility in completing tasks (from 30% to 85%), and empathy (from 20% to 70%). These results indicate that teachers’ consistency in modeling positive behavior effectively motivated students to adopt such behavior, creating a more conducive classroom environment. Thus, this study highlights the exemplary method as an effective strategy in fostering student character, particularly in the aspects of religiosity, discipline, honesty, responsibility, and empathy. The success of this approach was further reinforced by the supportive school culture and parental involvement in strengthening character values at home.